2006
DOI: 10.1590/s0100-83582006000200003
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da degradação da biomassa de três espécies de plantas aquáticas no reservatório da UHE de Americana-SP

Abstract: RESUMO -O estudo de decomposição de plantas aquáticas foi realizado na UHE de Americana-CPFL, com o objetivo de avaliar a taxa de degradação de plantas na própria água do reservatório. Foram consideradas como variáveis a profundidade (superfície, 3,5 e 7,0 m), as espécies de plantas aquáticas (Eichhornia crassipes, Brachiaria subquadripara e Pistia stratiotes) e o tipo de processamento a que estas foram submetidas (planta inteira, planta picada manualmente e com aplicação de fogo). Este estudo indicou que as e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…When it becomes dominant, invasive Poaceae (like U. arrecta) makes stands practically mono-specific, lowering biotic heterogeneity and changing habitat complexity (Negrisoli et al, 2006). In a recent investigation in streams on the coast of the State of São Paulo, Amorim (2012) showed that native macrophyte richness in patches dominated by U. subquadripara were much lower than in patches dominated by a native species (Eichhornia azurea Kunth), indicating impacts of the invasive species.…”
Section: Resultsmentioning
confidence: 99%
“…When it becomes dominant, invasive Poaceae (like U. arrecta) makes stands practically mono-specific, lowering biotic heterogeneity and changing habitat complexity (Negrisoli et al, 2006). In a recent investigation in streams on the coast of the State of São Paulo, Amorim (2012) showed that native macrophyte richness in patches dominated by U. subquadripara were much lower than in patches dominated by a native species (Eichhornia azurea Kunth), indicating impacts of the invasive species.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of heterogeneity, which was also shown in other investigations (Negrisoli et al . , Aday ), is enhanced by the absence of native macrophytes in the more extensively developed patches of U. arrecta (see Fig. A), which become monospecific.…”
Section: Discussionmentioning
confidence: 97%
“…These include hampering navigation and water extraction, jeopardizing electrical energy production and leisure activities, obstructing water flow in irrigation canals and contributing to the reduction of dissolved oxygen in the water. [8][9][10][11] The use of macrophytes for whatever means depends on determining several physicochemical properties typical to the intended application and the accumulated pollution content, as well as compliance with legislation. The application of macrophytes for nutrient removal in temporary rivers that appear during the dry season and where pollution content is seasonal has not yet been fully studied.…”
Section: Introductionmentioning
confidence: 99%